The Festival of Pirs: Popular Islam and Shared Devotion in South India, by Afsar Mohammad - Sijapati, Megan Adamson (Religions of South Asia, 2018)
The Festival of Pirs: Popular Islam and Shared Devotion in South India, by Afsar Mohammad. New York: Oxford University Press, 2013. x +100 pp., $125 (hb), $29.95 (pb). ISBN 978-0-19999-758-9 (hb), 978-0-19999-759-6 (pb).